2012
DOI: 10.1175/jamc-d-11-0173.1
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Regression Retrieval Algorithm for Real-Time Processing of Satellite Ultraspectral Radiances

Abstract: A fast physically based dual-regression (DR) method is developed to produce, in real time, accurate profile and surface- and cloud-property retrievals from satellite ultraspectral radiances observed for both clear- and cloudy-sky conditions. The DR relies on using empirical orthogonal function (EOF) regression “clear trained” and “cloud trained” retrievals of surface skin temperature, surface-emissivity EOF coefficients, carbon dioxide concentration, cloud-top altitude, effective cloud optical depth, and atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 27 publications
2
58
0
Order By: Relevance
“…However, the algorithm is known to produce reasonably good results for optically thin cloud conditions (Weisz et al 2007b). Thus, in order to filter out grid points with thick clouds, we obtain cloud thickness values using the University of Wisconsin's AIRS regression retrieval algorithm package (UWAIRS, version 3.0; Smith et al 2012). This algorithm uses a dual-regression technique that determines the presence of a cloud and associated cloud-thickness value based on the differences between clear-trained and cloudy-trained solutions at each grid point (Smith et al 2012).…”
Section: Airs Data Retrievalsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the algorithm is known to produce reasonably good results for optically thin cloud conditions (Weisz et al 2007b). Thus, in order to filter out grid points with thick clouds, we obtain cloud thickness values using the University of Wisconsin's AIRS regression retrieval algorithm package (UWAIRS, version 3.0; Smith et al 2012). This algorithm uses a dual-regression technique that determines the presence of a cloud and associated cloud-thickness value based on the differences between clear-trained and cloudy-trained solutions at each grid point (Smith et al 2012).…”
Section: Airs Data Retrievalsmentioning
confidence: 99%
“…Thus, in order to filter out grid points with thick clouds, we obtain cloud thickness values using the University of Wisconsin's AIRS regression retrieval algorithm package (UWAIRS, version 3.0; Smith et al 2012). This algorithm uses a dual-regression technique that determines the presence of a cloud and associated cloud-thickness value based on the differences between clear-trained and cloudy-trained solutions at each grid point (Smith et al 2012). The assigned cloud thickness values may range from 0 to 3, with 0 indicating clear or thin cloud conditions and 3 representing locations with thick clouds (Smith et al 2012).…”
Section: Airs Data Retrievalsmentioning
confidence: 99%
See 1 more Smart Citation
“…With AIRS as the HSRS, the CTP retrievals are derived at single-FOV resolution from the dual-regression (DR) retrieval method (Weisz et al 2011;Smith et al 2012). The DR method, which uses statistical datasets stratified by cloud heights, provides accurate profile, surface, and cloud-property retrievals from highspectral-radiance measurements under clear skies as well as below thin and/or scattered-to-broken cloud conditions.…”
Section: A Ctp/cth For Each Single Hsrs Fovmentioning
confidence: 99%
“…Past studies demonstrated the use of the hyperspectral IR bands for cloud-property retrieval (Zhou et al 2007(Zhou et al , 2009Weisz et al 2007b). An AIRS research algorithm that is based on eigenvector regression and was developed at the Cooperative Institute for Meteorological Satellite Studies/ University of Wisconsin-Madison is used to derive AIRS-only sounding profiles (temperature, moisture, and ozone) and simultaneously cloud-top pressure (CTP) at single AIRS FOV resolution (Weisz et al 2011;Smith et al 2012). Synergistic use of imager and sounder measurements has been shown to improve cloud-top retrievals at sounder resolution (Li et al 2004(Li et al , 2005.…”
Section: Introductionmentioning
confidence: 99%